Pengaruh Lokasi dan Promosi Terhadap Keputusan Pembelian Produk Merchendise: Studi Kasus Konsumen UNG Mart and Food Service - Frisilya Holle; Tineke Wolok; Umin Kango (Economic Reviews Journal, 2025)
Form the formulate objectives, this study aims to identify and analyze the influence of both location and promotion on purchase decisions for merchendise products. The method in this study is quantitative, and the data collection technique is through questionnaires. The sample consists of 96 respondents. The data analysis employs multiple linear regression analysis. This study indicates the following results. Partially, the location variable has a positive and significant influence on purchase decisions, with a t_count value of 2.634 > t_table of 1.661 and significance level of 0,000 < 0,05. Partially, the promotion variable has a positive and significant influence on purchase decisions, with a t_count value of 6,598 > t_table of 1.661 and a significance level of 0,000 < 0,05. Simultaneously, the variable of location and promotion have a positive and significant influence on purchase decisions, with a f_count value of 62,922 > f_table of 3,094 and significance level of 0,000 < 0,05. Additionally, the R square value is 0,575, indicating that 57,5% of the influence on purchase decisions is attributed to location and promotion, while the remaining 42,5% is influenced by other factors outside the research model.